Evaluation of bone and mineral metabolism in primary corticosteroid-sensitive pediatric nephrotic syndrome - Miguel Liern; Mario Alejandro Mullet Mendoza; Carlos Alberto Manotas Arciniegas; Graciela Vallejo (Revista de Nefrología, Diálisis y Trasplante, 2017)
Introduction: Steroid treatment for corticosteroid-sensitive nephrotic syndrome (CSNS) could cause bone and mineral metabolism alterations, preventable with calcium and Vitamin D. Objectives: We carried out a preliminary retrospective study along 36 months with the following objectives. 1) To evaluate the relationship between Cumulative Corticosteroid Doses (CCD) and 25-0 Vitamin D serum concentration and with Bone Mineral Content (BMC); 2) To evaluate the relationship between CCD and Bone Mineral Densitomety (BMD). Methods: We included patients between 2 and 12 years of age with corticosteroid sensitive primary nephrotic syndrome (CSNS) (first episode, relapsing nephrotic syndrome, corticosteroid dependent nephrotic syndrome) normotensive, eutrophic and FG>:90ml/min/1.73 m2, who were divided into three groups: GROUP A: =3 or <relapses/year, GROUP B: >4 relapses/year, GROUP C: CSNS, we measured: a) Quarterly: calcemia, phosphatemia, alkaline phosphatase; b) half-yearly: 25-OH cholecalcipherol levels, CCD; c) annually BMD in children >6 years (score Z and BMC), bone age, PTHi. Results: We evaluated 29 patients, average age: 4.4 years. The BMD was performed on 11 patients and there were no significant differences among the groups (p=0.08). No significant differences were seen between chronologic age and average bone age (p=0.3). Change in 25-OH cholecalcipherol levels due to the increase of ergocalcipherol dose was significant (T:32.4 Q:<0.001). There were significant correlation in the three groups, between Vitamin D dose and Vitamin D serum levels (Pearson correlation R=0.9), between CCD and 25 OH cholecalcipherol dose: (Pearson correlation R=0.62) and between CCD and BMC (Pearson correlation R=0.44). Finally, in these three groups the average increase of vitamin D was: 1833IU. Conclusions: We found a relationship between CCD and hypovitaminosis D, which could be corrected increasing Vitamin D dose.